Technology Design in Health Services: Feature Planning Strategy Filter for HMIS Optimization - Agus Widodo; Rokhman Handoyo; Abdul Hakim (Formosa Journal of Multidisciplinary Research, 2024)
Health information management in hospitals requires an efficient and structured system to accurately present patient data. This study aims to develop a filter feature in the Hospital Management Information System (HMIS) to enhance the efficiency of patient coding status management at Muhammadiyah Hospital. The development method involves a software development approach based on the Software Development Life Cycle (SDLC), involving medical record officers and administrative staff as the study population. The results show that the addition of the filter feature in HMIS successfully improves the efficiency of managing patient coding status. The filter feature enables medical record officers to easily identify the filling status of each patient efficiently, enhances the accuracy of health data management, and minimizes the risk of errors.